2020
DOI: 10.1039/c9ra08999c
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery decision algorithm trained by two-step machine learning algorithm

Abstract: A two-step machine learning (ML) algorithm for coronary artery decision making is introduced, to increase the data quality by providing flow characteristics and biometric features by aid of computational fluid dynamics (CFD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This study demonstrated that various imaging tools have been used, including CCTA [ 24 40 ], OCT [ 41 – 43 ], XCA [ 44 ], and IVUS [ 45 ]. Several studies used a combination of CCTA with OCT [ 46 ], IVUS [ 47 ], and XCA [ 48 ], and a study combined IVUS and XCA [ 49 ] to estimate the FFR. Most of the studies used CCTA to estimate the FFR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated that various imaging tools have been used, including CCTA [ 24 40 ], OCT [ 41 – 43 ], XCA [ 44 ], and IVUS [ 45 ]. Several studies used a combination of CCTA with OCT [ 46 ], IVUS [ 47 ], and XCA [ 48 ], and a study combined IVUS and XCA [ 49 ] to estimate the FFR. Most of the studies used CCTA to estimate the FFR.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies used CCTA to estimate the FFR. AI methods used include methods based on DL [ 25 , 27 – 29 , 34 , 40 , 41 , 48 ] and ML [ 26 , 42 , 30 , 32 , 33 , 37 , 39 , 44 , 46 , 49 ]. Some studies have used a combination of DL and ML techniques [ 24 , 32 , 37 , 38 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD-based blood flow simulation of reconstructed three-dimensional models was performed using the lattice Boltzmann method, which has been widely used for biofluidics; it uses lattice grids instead of complicated meshes for complex three-dimensional models ( 19 , 20 ). Blood was modeled as an incompressible non-Newtonian fluid with a density of 1,060 kg/m 3 based on the Carreau–Yasuda model ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a no-slip boundary condition was used to calculate the interaction between the vessel wall and blood flow. Detailed equations and numerical methods used for estimating CFD-based computational FFR have been described previously ( 20 ). For each patient, Fusion-FFR, CT-FFR, and OCT-FFR were estimated.…”
Section: Methodsmentioning
confidence: 99%